Electronic cigarette exposure on insulin sensitivity of ApoE gene knockout mice - Kai Lan+; Guangwei Zhang+; Lijuan Liu; Ziwei Guo; Xianyu Luo; Hua Guan; Qi Yu; Enqi Liu (Tobacco Induced Diseases, 2020)
Introduction The current study aimed to investigate the effects of electronic cigarettes on insulin sensibility in ApoE gene knockout mice.